Corrosion and chemical resistant masonry materials handbook - Sheppard, Walter Lee, 1911- (Noyes Publications, 1986)
Describes corrosion and chemical resistant masonry materials necessary for buildings and equipment requiring such materials. Covers a broad variety of materials, from structural materials, membranes, and lining systems, to inspection and failure analysis. This will enable practicing engineers and architects to write specifications and instructions, and to draw details, for installation of such masonry materials and equipment. It will also be of use to a wide variety of manufacturing and chemical process industries.
Keywords: Corrosion and anti-corrosives -- Handbooks, manuals, etc.; Masonry -- Materials -- Corrosion -- Handbooks, manuals, etc.; elektronické knihy; electronic books